Peripheral chemoreceptors and cardiorespiratory coupling: a link to sympatho-excitation - Zoccal, Daniel Breseghello [UNESP] (Wiley, 2015)
Chronic intermittent hypoxia (CIH) has been identified as a relevant risk factor for the development of enhanced sympathetic outflow and arterial hypertension. Several studies have highlighted the importance of peripheral chemoreceptors for the cardiovascular changes elicited by CIH. However, the effects of CIH on the central mechanisms regulating sympathetic outflow are not fully elucidated. Our research group has explored the hypothesis that the enhanced sympathetic drive following CIH exposure is, at least in part, dependent on alterations in the respiratory network and its interaction with the sympathetic nervous system. In this report, I discuss the changes in the discharge profile of baseline sympathetic activity in rats exposed to CIH, their association with the generation of active expiration and the interactions between expiratory and sympathetic neurones after CIH conditioning. Together, these findings are consistent with the theory that mechanisms of central respiratory–sympathetic coupling are a novel factor in the development of neurogenic hypertension.